Highly efficient local delivery of endothelial progenitor cells significantly potentiates angiogenesis and full-thickness wound healing - Wang, Chenggui; Wang, Qingqing; Gao, Wendong; Zhang, Zengjie; Lou, Yiting; Jin, Haiming; Chen, Xiaofeng; Lei, Bo; Xu, Huazi; Mao, Cong (Acta biomaterialia, 2018)
[Display omitted] Wound therapy with a rapid healing performance remains a critical clinical challenge. Cellular delivery is considered to be a promising approach to improve the efficiency of healing, yet problems such as compromised cell viability and functionality arise due to the inefficient delivery. Here, we report the efficient delivery of endothelial progenitor cells (EPCs) with a bioactive nanofibrous scaffold (composed of collagen and polycaprolactone and bioactive glass nanoparticles, CPB) for enhancing wound healing. Under the stimulation of CPB nanofibrous system, the viability and angiogenic ability of EPCs were significantly enhanced through the activation of Hif-1α/VEGF/SDF-1α signaling. In vivo, CPB/EPC constructs significantly enhanced the formation of high-density blood vessels by greatly upregulating the expressions of Hif-1α, VEGF, and SDF-1α. Moreover, owing to the increased local delivery of cells and fast neovascularization within the wound site, cell proliferative activity, granulation tissue formation, and collagen synthesis and deposition were greatly promoted by CPB/EPC constructs resulting in rapid re-epithelialization and regeneration of skin appendages. As a result, the synergistic enhancement of wound healing was observed from CPB/EPC constructs, which suggests the highly efficient delivery of EPCs. CPB/EPC constructs may become highly competitive cell-based therapeutic products for efficient impaired wound healing application. This study may also provide a novel strategy to develop bioactive cell therapy constructs for angiogenesis-related regenerative medicine. This paper reported a highly efficient local delivery of EPCs using bioactive glass-based CPB nanofibrous scaffold for enhancing angiogenesis and wound regeneration. In vitro study showed that CPB can promote the proliferation, migration, and tube formation of EPCs through upregulation of the Hif-1α/VEGF/SDF-1α signaling pathway, indicating that the bioactivity and angiogenic ability of EPCs can be highly maintained and promoted by the CPB scaffold. Moreover, CPB/EPC constructs effectively stimulated the regeneration of diabetic wounds with satisfactory vascularization and better healing outcomes in a full-thickness wound model, suggesting that the highly efficient delivery of EPCs to wound site facilitates angiogenesis and further leads to wound healing. The high angiogenic capacity and excellent healing ability make CPB/EPC constructs highly competitive in cell-based therapeutic products for efficient wound repair application.